Public health care system, a quasi-experimental study: Acceptance and attitude to implicate clinical services - Gillani Syed Wasif; Abdul Mohi Iqbal Mohammad (Acta Pharmaceutica)
A six-month longitudinal intervention arm study with a pre-post cross-sectional questionnaire-based survey was performed. A 3-phase objective structured clinical examination (OSCE) design was utilized for evaluation of acceptance and attitude of pharmacy students towards clinical pharmacy services. The pre-OSCE survey showed increased disagreement with the role of clinical pharmacists, compared to a significant positive shift in attitude towards their services in the healthcare team after 6 months of the trial. Responses improved for awareness (the current healthcare system could be improved by involving pharmacists, p < 0.02) and positive attitude categories (doctors and nurses would be happy to welcome the services of competent clinical pharmacists as part of their team, p < 0.01) in addition to competency (pharmacists have sufficient clinical training to advise doctors and nurses, p < 0.01). The predictive model suggested a strong positive effect on patient interaction, medical information tasks, clinical decisions on drug-related problems (DRPs), and communication with healthcare professionals (R2 = 0.41, F = 1.51, p < 0.001).